A New Heuris tic for Multiplication of two matrices of order 2*2 - Debnath, Shankar; Nath, Ira; Singh, Dharmpal (International Journal of Computer Sciences and Engineering, 2025)
From the very beginning of computer era, the scientists are trying their best for searching the method which can reduce the complexity of multiplication of matrices. In case of ordinary matrix multiplication of two given 2*2 matrixes, we use three for loops to determine the product of these two matrixes and produce a resultant two-dimensional matrix. Then the complexity of the algorithm is n3. Although this problem has been studying extensively, we intend to implement and modify the pre-existing procedure. So, we decide to tackle the multiplication of those two two-dimentional matrixes by using a one- dimensional array. The algorithm that we develop will store all the elements of two 2x2 matrixes in a single one-dimensional array. Then we generalized a formula that will provide the co-relationship between the index number of the one-dimensional array to find the product of those two 2*2 matrixes. So, in our case we determine the result by using two for loops only that basically reduce the complexity.